The effect of posterior vitreous detachment induced by intravitreal injections on macular edema with retinal vein occlusion - Akincioglu, Dorukcan; Kucukevcilioglu, Murat; Durukan, Ali Hakan (Indonesian Vitreoretinal Society, 2021)
Introduction: To evaluate whether posterior vitreous detachment (PVD) improves treatment outcomes.Methods:The medical records of treatment-naive patients followed up for a minimum of six months due to retinal vein occlusion between January 2007 and January 2016 were reviewed. Patients with initial PVD were excluded. Correlation analysis and binary logistic regression analysis were used to determine the relationship between categorical variables and treatment outcomes. A subgroup analysis (steroids vs anti-VEGFs) was also performed.Results: The study included 95 eyes of 95 patients with macular edema due to retinal vein occlusion. Patients in both groups [central retinal vein occlusion (CRVO) and branch retinal vein occlusion (BRVO)] were similar in terms of demographic data and showed similar improvement during the study. The patients who underwent intravitreal steroid injection (IVD or IVTA) were 12.35 times (95% CI: 4.03-37.85) more likely to develop PVD. The patients in steroid group had a statistically significantly high correlation with visual and anatomic improvements, especially after 5 months of follow-up. The median time of PVD was 5 months (2-11).Conclusion: Commonly used drugs in intravitreal pharmacotherapy induce PVD, which plays an important role for the treatment of underlying macular edema.